Effect of Using Cow Dung as Organic Fish Pellets - Marten, Threo Wanda; Razak, Abdul; Barlian, Eri; Kamal, Eni (Poltekita : Jurnal Ilmu Kesehatan, 2024)
Freshwater cultivation is an economic endeavor for welfare purposes and is currently facing problems. This problem occurs because pellets are not economical and cause environmental pollution. The purpose of this article is to analyze the effect of using cow dung as fish pellets on Abiotic, Biotic, and Cultural (Human Habits). This research is a Quantitative Experimental Research using a Completely Randomized Design (CRD) of 4 treatments with 6 replications, treatment in the form of feeding 3 g/day (Treatment 2) 6 g/day (Treatment 3) 9 g/day (Treatment 4) and Control (Treatment 1) uses chemical pellets 9 g/day. This design is used to see the effect of organic fish pellets on fish growth (biotic) such as fish weight and length. The hypothesis of this research is H1: There is an influence, H0: There is no influence. Hypothesis H1 is accepted if F count > F table. Then a measuring instrument is used to measure environmental parameters such as temperature, DO, pH, and Ammonia. The results of this research reveal: there is an influence of fish pellets on fish growth (Biotic), the use of cow dung pellets is still safe in the aquatic environment (Abiotic), cow dung pellets provide socio-economic value such as increasing income and creating new productive habits by making it a job. This research concludes that the use of cow dung pellets reduces environmental pollution, is economical, and is beneficial for humans. It is recommended that this research be further deepened and linked to other sciences.